Heterologous vaccine immunogenicity, efficacy, and immune correlates of protection of a modified-live virus porcine reproductive and respiratory syndrome virus vaccine - Proctor, Jessica; Wolf, Iman; Brodsky, David; Cortes, Lizette M.; Frias-De-Diego, Alba; Almond, Glen W.; Crisci, Elisa; Negrão Watanabe, Tatiane Terumi; Hammer, James M.; Käser, Tobias (Frontiers in Microbiology, 2022)
Although porcine reproductive and respiratory syndrome virus (PRRSV) vaccines have been available in North America for almost 30 years, many vaccines face a significant hurdle: they must provide cross-protection against the highly diverse PRRSV strains. This cross-protection, or heterologous vaccine efficacy, relies greatly on the vaccine’s ability to induce a strong immune response against various strains – heterologous immunogenicity. Thus, this study investigated vaccine efficacy and immunogenicity of a modified live virus (MLV) against four heterologous type 2 PRRSV (PRRSV-2) strains. In this study, sixty pigs were divided into ten groups. Half were MOCK-vaccinated, and the other half vaccinated with the Prevacent® PRRS MLV vaccine. Four weeks after vaccination, groups were challenged with either MOCK, or four PRRSV-2 strains from three different lineages – NC174 or NADC30 (both lineage 1), VR2332 (lineage 5), or NADC20 (lineage 8). Pre-and post-challenge, lung pathology, viral loads in both nasal swabs and sera, anti-PRRSV IgA/G, neutralizing antibodies, and the PRRSV-2 strain-specific T-cell response were evaluated. At necropsy, the lung samples were collected to assess viral loads, macroscopical and histopathological findings, and IgA levels in BAL. Lung lesions were only induced by NC174, NADC20, and NADC30; within these, vaccination resulted in lower gross and microscopic lung lesion scores of the NADC20 and NADC30 strains. All pigs became viremic and vaccinated pigs had decreased viremia upon challenge with NADC20, NADC30 and VR2332. Regarding vaccine immunogenicity, vaccination induced a strong systemic IgG response and boosted the post-challenge serum IgG levels for all strains. Furthermore, vaccination increased the number of animals with neutralizing antibodies against three of the four challenge strains – NADC20, NADC30, and VR2332. The heterologous T-cell response was also improved by vaccination: Not only did vaccination increase the induction of heterologous effector/memory CD4 T cells, but it also improved the heterologous CD4 and CD8 proliferative and/ or IFN-γ response against all strains. Importantly, correlation analyses revealed that the (non-PRRSV strain-specific) serum IgG levels and the PRRSV strain-specific CD4 T-cell response were the best immune correlates of protection. Overall, Prevacent elicited various degrees of efficacy and immunogenicity against four heterologous and phylogenetically distant strains of PRRSV-2.